Pengaruh Model Pembelajaran Interaktif Menggunakan Lumi Education untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Informatika - Permana, Muhammad Sakha; Setiawan, Dena Latif (Indo-MathEdu Intellectuals Journal, 2024)
The use of technology in the world of education, especially learning applications, is increasingly important in supporting an effective and efficient learning process. Media Lumi Education was chosen because of its interactive features that are expected to improve learning outcomes. This study aims to analyze the influence of the introduction of Lumi Education learning media on the learning outcomes of grade VII students in informatics subjects at SMP Negeri 1 Pancalang. The research method used is pre-experiment with pre-test and post-test design for one class. Data collection was carried out through pre-test and post-test scores in the form of 10 questions. Data analysis was carried out using a t-test. The findings of the study show that student learning outcomes increased after the implementation of Lumi Education learning media at SMP Negeri 1 Pancalang. There was a significant difference in student learning outcomes before and after using Lumi Education learning media Based on the results of descriptive analysis, the average student pretest scores were 55.20 and 75.20 points. And the results of the paired sample t-test showed that the significant value was 0.000 which was smaller than 0.05. Thus, it can be concluded that Ho was rejected and H1 was accepted. And it shows that there is an influence on student learning outcomes using Lumi Education media